Prevalence of obesity and overweight in uruguayan children during the last 20 years: review of the national bibliography (Archives of Pediatrics of Uruguay, 2020)
Introduction: there is national concern regarding the prevalence of obesity and overweight in Uruguayan children in the last few decades.Objectives: describe the prevalence of obesity and overweight in Uruguayan children in the last 19 years based on the research work published.Material and method: different databases were analyzed in order to research the prevalence of obesity and overweight in children of under 18 years of age in Uruguay between 2000 and 2018. We compared 2 periods: 2000- 2009 and 2010- 2018, for the case of children of under and over 5 years of age. We compared the weighted means for each period and age range and described the prevalence by gender.Results: we analyzed 6 studies between 2000 and 2009 and 11 between 2010 and 2018. In the first period, for children of under 5 years of age, the reported obesity/overweight prevalence showed a weighted mean of 7.7%; for children older than 5 years of age, it was 15% for excess weight and 8.3% for obesity. In the second period, for children under 5 years of age, the prevalence of obesity/overweight was 11.5% (weighted mean); for the case of children older than 5 years of age, the mean overweight prevalence was 25.2% and the mean obesity prevalence, 9.7%. The comparison of both weighted means’ prevalences showed significant differences.Conclusions: there was an increase in the prevalence of obesity/overweight for the case of children of under 5 years of age. For children older than 5 years of age, both prevalence figures rose significantly.
Keywords: Overweight; Obesity; Child; Adolescent; Prevalence; Risk factors